Factors influencing patients' choice of clinic at Inanda, KwaZulu-Natal - Zethembiso C. Hlongwa; Saajida Mahomed (AOSIS, 2021)
Background: In South Africa, patients are meant to attend the clinic close to their place of residence. However, patients often choose which clinic to attend, which results in overcrowding. Aim: This study aimed to investigate the structural and process factors influencing patients' choice to attend a community health centre (CHC) in KwaZulu-Natal, South Africa. Setting: The study was conducted at the Inanda C Community Health Centre (CHC). Methods: Systematic random sampling was used to select study participants. A structured questionnaire was used to collect socio-demographic data and assess the factors influencing patients' choice to attend this CHC. Results: There were 400 patients who participated. The commonest structural indicator that patients agreed on as the reason they attend Inanda C CHC was because it has enough medication (126, 73.3%). There was a significant difference in the proportion of patients who agreed that seeing a doctor instead of nurse was a reason for attending this clinic with 118 (68.6%) patients from within the catchment area and 170 (74.6%) from outside the catchment area. The commonest process indicators that patients from within and outside the catchment area agreed on as reasons for attending Inanda C CHC were 'the doctor or nurse explains my sickness and treatment to me' and 'I get good quality of care'. Conclusion: The structural and process indicators that influence patients' choice of clinic may need to be improved at other clinics in this area in order to decrease the overcrowding at this clinic.